2016
DOI: 10.4103/0974-1208.183512
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic screening for all 24 chromosomes by microarray comparative genomic hybridization significantly increases implantation rates and clinical pregnancy rates in patients undergoing in vitro fertilization with poor prognosis

Abstract: CONTEXT:A majority of human embryos produced in vitro are aneuploid, especially in couples undergoing in vitro fertilization (IVF) with poor prognosis. Preimplantation genetic screening (PGS) for all 24 chromosomes has the potential to select the most euploid embryos for transfer in such cases.AIM:To study the efficacy of PGS for all 24 chromosomes by microarray comparative genomic hybridization (array CGH) in Indian couples undergoing IVF cycles with poor prognosis.SETTINGS AND DESIGN:A retrospective, case–co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…During the process of IVF, morphological evaluations of embryos and preimplantation genetic screening are conducted for best embryo selection. Recently, as more precise and less invasive genetic screening methods have been developed (23,24), pregnancy outcomes have improved (24,25). The introduction of more-advanced genetic screening to IVF clinics may have contributed to a comparable or even lower incidence of congenital anomalies in VLBW infants born after IVF in our study.…”
Section: Discussionmentioning
confidence: 68%
“…During the process of IVF, morphological evaluations of embryos and preimplantation genetic screening are conducted for best embryo selection. Recently, as more precise and less invasive genetic screening methods have been developed (23,24), pregnancy outcomes have improved (24,25). The introduction of more-advanced genetic screening to IVF clinics may have contributed to a comparable or even lower incidence of congenital anomalies in VLBW infants born after IVF in our study.…”
Section: Discussionmentioning
confidence: 68%
“…Controlled ovarian stimulation, oocyte retrieval and intracytoplasmic sperm injection (ICSI) were performed as previously reported. [ 25 ] Fertilization was checked at 16–18 h post ICSI. Embryo culture was undertaken in sequential culture media (Vitrolife, Sweden) to blastocyst stage, wherein 2pn embryos were cultured in groups of up to 6–8 embryos in 0.7 ml of G1P under oil (Vitrolife, Sweden) from day 1 to day 3 and G2P under oil (Vitrolife, Sweden) from day 3 to day 5.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…[ 8 9 10 11 12 ] Contrastingly, the advent of PGS in the form of comprehensive chromosomal screening (CCS) for all 24 chromosomes using newly validated platforms[ 13 14 15 16 17 18 ] is proving to be a promising approach for improving clinical outcomes in IVF, as evidenced by recent studies that showed that biopsy at the cleavage stage or the blastocyst stage followed by CCS resulted in improved embryo selection as compared to traditional morphology-based selection alone. [ 19 20 21 22 23 24 25 ] Furthermore, the combination of trophectoderm (TE) biopsy followed by blastocyst vitrification and CCS has not only resulted in an improvement in clinical outcomes, but is also allowing infertile women, even of advanced maternal age (AMA),[ 24 ] to adopt single-embryo transfers (SETs) as a viable option without lowering success rates.…”
Section: Introductionmentioning
confidence: 99%
“…Preimplantation genetic testing for aneuploid (PGT-A) and preimplantation genetic testing for chromosomal structural rearrangement (PGT-SR) were widely used to screen embryos' genetic condition prior to transfer for advanced maternal age couples, recurrent implantation failure, recurrent miscarriage patients and chromosome structure abnormality carrier patients [12]. It has been found that transfer of PGT-screened normal blastocysts could signi cantly increase implantation and reduce pregnancy loss [13][14][15]. Hence, these techniques were widely used in chromosomal and genetic disease diagnosis.…”
Section: Introductionmentioning
confidence: 99%